A LTA structure hollow aluminum phosphate molecular sieve and its preparation method and application

By using the nano aluminum phosphate molecular sieve parent template and suitable template agent for secondary crystallization and etching under hydrothermal conditions, hollow aluminum phosphate molecular sieve with LTA structure was prepared, which solved the problem of limited diffusion of molecular sieve micropores and improved the selectivity and activity of the catalyst.

CN118894539BActive Publication Date: 2025-03-21LIAOCHENG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410931050.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-11
Publication Date
2025-03-21
Estimated Expiration
2044-07-11

AI Technical Summary

Technical Problem

The micropores of the molecular sieve will lead to the problem of limited diffusion of substances while selecting shapes, and the selectivity and activity of the catalyst are insufficient.

Method used

Nano-aluminum phosphate molecular sieve is used as the parent template, and post-treatment is carried out under hydrothermal conditions, and a suitable template agent is selected for secondary crystallization and etching to prepare a hollow aluminum phosphate molecular sieve with an LTA structure.

Benefits of technology

It improves the selectivity and activity of the catalyst, increases the specific surface area, exposes more active sites, promotes the diffusion of guest molecules, and shortens the mass transfer pathway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118894539B_ABST
    Figure CN118894539B_ABST
Patent Text Reader

Abstract

The invention discloses a hollow aluminum phosphate molecular sieve with an LTA structure and a preparation method and application thereof, belonging to the technical field of molecular sieve porous materials, and provides a preparation method of a hollow aluminum phosphate molecular sieve with an LTA structure, comprising the following steps: mixing deionized water, an aluminum source, an aqueous phosphoric acid solution and an aqueous hydrofluoric acid solution to obtain a premixed solution, dripping propylene oxide, sequentially impregnating a double template agent to obtain a hydrogel, drying to obtain an aluminum phosphate dry gel, first crystallization, drying to obtain a nano aluminum phosphate molecular sieve powder, placing it in an aqueous template agent solution, second crystallization, separating a solid product, and roasting to obtain a hollow aluminum phosphate molecular sieve with an LTA structure. The hollow aluminum phosphate molecular sieve with an LTA structure prepared by the invention has both micropores and mesopores, and has the characteristics of a large specific surface area, a large number of exposed active sites, fast diffusion of guest molecules, and a high mass transfer rate, thereby effectively improving the selectivity and activity of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve porous materials, and in particular relates to a LTA structure hollow aluminum phosphate molecular sieve and a preparation method and application thereof. Background Art

[0002] Molecular sieve is a synthetic crystalline microporous material or natural zeolite with the function of screening molecules. It is formed by silicon-oxygen tetrahedrons or aluminum-oxygen tetrahedrons connected by oxygen bridge bonds. Due to its regular pore structure, adjustable active sites, good hydrothermal stability, high specific surface area and large pore volume, it has important applications in adsorption separation, catalysis, ion exchange and energy storage. According to the skeleton composition of molecular sieves, they can be divided into three main families: silicate molecular sieves (silicon aluminum, boron silicon, titanium silicon and silicon germanium, etc.), phosphate molecular sieves (aluminum phosphate, heteroatom aluminum phosphate and gallium phosphate, etc.) and other non-tetrahedral molecular sieves. Among them, AlPO-42 has The aluminum phosphate molecular sieve has a three-dimensional pore structure of LTA (International Molecular Sieve Association designated code) cage and 8-membered ring. Because its pore structure is uniform and regular, comparable to the molecular size, it has a huge specific surface area, and has good hydrothermal stability and weak acid catalytic activity, and can be used as an adsorbent and catalyst carrier. However, the micropores of the molecular sieve will bring about the problem of limited diffusion of substances while selecting the shape. Designing and constructing hollow molecular sieves can introduce more mesopores on the basis of micropores, improve the diffusion capacity of guest molecules, shorten the mass transfer path, expose more active sites, and improve the selectivity of the catalyst. It is not only an effective way to solve the problem of diffusion limitation, but also improves the life of the catalyst, and has great application prospects in industry. Summary of the invention

[0003] In order to solve the above technical problems, the present invention proposes a hollow aluminum phosphate molecular sieve with LTA structure and a preparation method and application thereof. The present invention uses nano aluminum phosphate molecular sieve as a mother template, selects a suitable template agent to play a structural guiding role in secondary crystallization and also plays a role as an etchant, and performs post-treatment under hydrothermal conditions to prepare a hollow aluminum phosphate molecular sieve with LTA structure. The hollow aluminum phosphate molecular sieve with LTA structure prepared by the present invention has both micropores and mesopores, and has the characteristics of large specific surface area, many exposed active sites, fast diffusion of guest molecules, high mass transfer rate, etc., thereby effectively improving the selectivity and activity of the catalyst.

[0004] To achieve the above object, the present invention provides a method for preparing a hollow aluminum phosphate molecular sieve with an LTA structure, comprising the following steps:

[0005] (1) deionized water, an aluminum source, an aqueous phosphoric acid solution, and an aqueous hydrofluoric acid solution are mixed, and stirred for the first time under an ice bath condition to obtain a premixed solution; propylene oxide (PO) is added dropwise to the premixed solution, and stirred for the second time, and then dual template agents are sequentially impregnated, and stirred for the third time under a sealed condition to obtain a hydrogel;

[0006] (2) The hydrogel of step (1) is first dried to obtain aluminum phosphate xerogel;

[0007] (3) the aluminum phosphate dry gel in step (2) is first crystallized and dried to obtain nano aluminum phosphate molecular sieve powder;

[0008] (4) placing the nano aluminum phosphate molecular sieve powder described in step (3) in a template aqueous solution, performing a second crystallization, separating the solid product, performing a second drying, and then calcining to obtain a LTA structure hollow aluminum phosphate molecular sieve.

[0009] Preferably, the aluminum source in step (1) is one of crystalline aluminum chloride, pseudo-boehmite or aluminum isopropoxide.

[0010] Preferably, the concentration of the phosphoric acid aqueous solution in step (1) is 70 to 99 wt %, and the concentration of the hydrofluoric acid aqueous solution in step (1) is 30 to 70 wt %.

[0011] Preferably, in step (1), the speed of the first stirring is 5 to 1000 r / min, the temperature of the first stirring is -5 to 15°C, and the time of the first stirring is 1 to 360 min; the speed of the dripping in step (1) is 2 to 270 drops / min; the temperature of the second stirring in step (1) is 6 to 80°C, the speed of the second stirring is 5 to 1000 r / min, and the time of the second stirring is 1 to 360 min; the temperature of the third stirring in step (1) is 8 to 85°C, the speed of the third stirring is 3 to 1000 r / min, and the time of the third stirring is 1 to 360 min. The time interval is 1 to 600 min; the molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel in step (1) is 1:0.02-50.0:0.002-5.0:0.2-100.0:0.5-1000.0; the dual template agent in step (1) is two of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, 1-ethyl-3-methylimidazole hydroxide, 1-butyl-3-methylimidazole hydroxide, 1-propyl-3-methylimidazole hydroxide or 1-pentyl-3-methylimidazole hydroxide, and they are immersed in the two dual template agents in turn.

[0012] Preferably, the temperature of the first drying in step (2) is 50-150° C., and the time of the first drying is 0.5-24 h; the molar ratio of Al2O3:P2O5:HF:PO:H2O in the aluminum phosphate dry gel in step (2) is 1:0.02-50.0:0.002-5.0:0.2-100.0:0.1-50.0.

[0013] Preferably, in step (3), the temperature of the first crystallization is 90-300° C., and the time of the first crystallization is 1-240 h; the temperature of the drying in step (3) is 25-200° C., and the time of the drying is 0.5-36 h.

[0014] Preferably, the concentration of the template in the template aqueous solution in step (4) is 0.001 to 100.0 mol / L, and the template is one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, di-n-butylamine, 1-ethyl-3-methylimidazole hydroxide, 1-butyl-3-methylimidazole hydroxide, 1-propyl-3-methylimidazole hydroxide or 1-pentyl-3-methylimidazole hydroxide.

[0015] Preferably, the temperature of the second crystallization in step (4) is 25-300°C, and the time of the second crystallization is 0.5-240h; the temperature of the second drying in step (4) is 25-200°C, and the time of the second drying is 0.5-36h; the calcination in step (4) is carried out in air, the calcination temperature is 120-1000°C, and the calcination time is 1-48h.

[0016] The present invention also provides a hollow aluminum phosphate molecular sieve with an LTA structure prepared by the preparation method.

[0017] The present invention also provides the use of the LTA structure hollow aluminum phosphate molecular sieve or the LTA structure hollow aluminum phosphate molecular sieve prepared by the preparation method in heterogeneous catalysis.

[0018] Compared with the prior art, the present invention has the following advantages and technical effects:

[0019] The present invention, under the participation of propylene oxide (PO), mixes the reaction raw materials of deionized water, aluminum source, phosphoric acid and hydrofluoric acid uniformly, impregnates two dual templates in sequence to prepare hydrogel, performs aging and drying, and obtains aluminum phosphate dry gel. The dry gel is placed in a polytetrafluoroethylene liner to crystallize the obtained product, and then separated and dried to obtain powder. The powder is placed in a template and water, and heated for secondary crystallization to synthesize a hollow aluminum phosphate molecular sieve with an LTA structure. The present invention provides a preparation method of a hollow aluminum phosphate molecular sieve with an LTA structure. Using a nano aluminum phosphate molecular sieve as a mother template, post-treatment is performed under hydrothermal conditions to prepare a hollow aluminum phosphate molecular sieve with an LTA structure, wherein a suitable template is selected to play a structural guiding role of secondary crystallization and an etching agent. It has the advantages of simple operation steps, low cost, environmental friendliness, and easy industrial application. The hollow aluminum phosphate molecular sieve with the LTA structure has both micropores and mesopores, and has the characteristics of large specific surface area, many exposed active sites, fast diffusion of guest molecules, high mass transfer rate, etc., thereby effectively improving the selectivity and activity of its catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 The XRD spectrum of the LTA structure hollow aluminum phosphate molecular sieve synthesized in Example 1 of the present invention;

[0022] Figure 2 This is a SEM image of the LTA structure hollow aluminum phosphate molecular sieve synthesized in Example 1 of the present invention, with a scale of 200 nm;

[0023] Figure 3 This is the argon adsorption-desorption isotherm diagram of the LTA structure hollow aluminum phosphate molecular sieve synthesized in Example 1 of the present invention after calcination. DETAILED DESCRIPTION

[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0025] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0029] Example 1

[0030] 1) 4.86 g of crystalline aluminum chloride, 0.046 g of phosphoric acid aqueous solution (85 wt%) and 0.004 g of hydrofluoric acid aqueous solution (40 wt%) were added to 7.2 g of deionized water in sequence, and the mixture was stirred at 5 r / min for 5 min in an ice bath at 0° C. to obtain a premixed solution; 0.46 g of propylene oxide (PO) was added dropwise at 2 drops / min to the premixed solution, and the mixture was stirred at 10 r / min for 10 min at 20° C., and then 2.8 g of tetraethylammonium hydroxide (TEAOH) and 12 g of 1-butyl-3-methylimidazole hydroxide ([Bmim]OH) were impregnated in sequence, and the mixture was covered with a PE film to produce a sealing condition, and the mixture was stirred at 10 r / min for 30 min at 20° C. to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel is 1:0.02:0.002:0.2:10 (the molar amounts of the aluminum source and the phosphorus source are calculated in the form of their oxides).

[0031] 2) The hydrogel was placed in a mold with a diameter of 9 cm and dried at 50° C. for 6 h to obtain aluminum phosphate dry gel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the aluminum phosphate dry gel was 1:0.02:0.002:0.2:5 (the molar amounts of the aluminum source and the phosphorus source were calculated according to their oxide forms).

[0032] 3) 0.50 g of aluminum phosphate dry gel was placed in a 30 mL polytetrafluoroethylene liner, first crystallized at 100° C. for 10 h, and dried at 80° C. for 3 h, to finally obtain nano aluminum phosphate molecular sieve powder.

[0033] 4) 0.30 g of nano aluminum phosphate molecular sieve powder was placed in 5.0 g of tetraethylammonium hydroxide (TEAOH) aqueous solution (the concentration of the template agent tetraethylammonium hydroxide was 0.10 mol / L), and the second crystallization was performed at 100° C. for 8 h. The solid product was separated, second dried at 80° C. for 3 h, and calcined at 500° C. for 7 h to obtain a LTA structure hollow aluminum phosphate molecular sieve.

[0034] The LTA-structured hollow aluminum phosphate molecular sieve prepared in Example 1 was characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and argon physical adsorption technology to obtain the structure, morphology, specific surface area and pore structure information of the molecular sieve.

[0035] The results are as follows, Figure 1 This is the XRD diagram of the hollow aluminum phosphate molecular sieve prepared in Example 1, showing strong diffraction peaks at 2θ=7.41°, 10.49°, 12.85°, 22.38°, and 24.78°, with characteristic peaks of AlPO-42. Compared with the JCPDS standard card, it belongs to the LTA topological structure, has a stable baseline, no impurities, and good crystallinity.

[0036] Figure 2 This is a SEM photograph of the hollow aluminum phosphate molecular sieve prepared in Example 1. As shown in the figure, the morphology is complete, the surface is rough, and it has an obvious cubic shape. At the same time, most of the crystals are 30-50nm in size, which are nanomaterials; a small part is 160-250nm in size; the contrast of different light and dark crystals can be seen, and analysis shows that there are voids inside the prepared aluminum phosphate molecular sieve.

[0037] Figure 3 This is the argon adsorption-desorption isotherm of the hollow aluminum phosphate molecular sieve prepared in Example 1 after calcination. The structural properties of the sample after calcination were analyzed using argon adsorption technology to obtain specific surface area and pore structure information. According to the IUPAC classification, the argon adsorption-desorption isotherm of the hollow aluminum phosphate molecular sieve prepared in Example 1 is Figure 3It has the typical characteristics of type I + IV adsorption isotherm. The adsorption capacity increases rapidly with the slight change of relative pressure at 0.0 < P / P0 < 0.1, which is related to micropore filling; while at 0.1 < P / P0 < 0.4, the adsorption capacity changes slowly with the relative pressure, presenting a plateau region, indicating a microporous structure with monolayer or quasi-monolayer adsorption; at 0.4 < P / P0 < 0.9, due to capillary condensation, an H4-type hysteresis loop appears, analyzing that the material has mesoporous characteristics; when P / P0 is close to 1.0, adsorption occurs on macropores and the curve rises. Argon physical adsorption characterizes that the hollow aluminophosphate molecular sieve prepared in Example 1 has the multi-level pore characteristics of micropores, mesopores and macropores. The total specific surface area calculated by the BET method is 639 m 2 / g. This is beneficial to the progress of heterogeneous catalysis, can solve the problem of limited molecular diffusion in traditional microporous zeolite molecular sieves, and can effectively improve the catalyst activity.

[0038] Example 2

[0039] 1) 4.86 g of crystalline aluminum chloride, 0.46 g of phosphoric acid aqueous solution (85 wt%) and 0.04 g of hydrofluoric acid aqueous solution (40 wt%) were successively added to 7.2 g of deionized water. In an ice bath at 0 °C, it was first stirred at 10 r / min for 10 min to obtain a premixed solution; 1.16 g of propylene oxide (PO) was gradually added dropwise to the premixed solution at 20 drops / min. At 25 °C, it was second stirred at 15 r / min for 40 min, and then 5 g of tetramethylammonium hydroxide (TMAOH) and 10 g of 1-butyl-3-methylimidazolium hydroxide ([Bmim]OH) were successively impregnated. The PE film was covered to create a sealed condition. At 25 °C, it was third stirred at 15 r / min for 60 min to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel was 1:0.2:0.02:0.5:10 (the molar amounts of the aluminum source and the phosphorus source were calculated according to their oxide forms).

[0040] 2) The hydrogel was placed in a mold with a diameter of 9 cm and dried at 60 °C for 5 h to obtain an aluminophosphate xerogel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the aluminophosphate xerogel was 1:0.2:0.02:0.5:5 (the molar amounts of the aluminum source and the phosphorus source were calculated according to their oxide forms).

[0041] 3) 0.50 g of the aluminophosphate xerogel was placed in a 30 mL polytetrafluoroethylene inner liner, crystallized at 120 °C for 8 h, and dried at 80 °C for 3 h to finally obtain nano-sized aluminophosphate molecular sieve powder.

[0042] 4) 0.30 g of nano aluminum phosphate molecular sieve powder was placed in 5.0 g of tetramethylammonium hydroxide (TMAOH) aqueous solution (the concentration of the template agent tetramethylammonium hydroxide was 0.10 mol / L), and the second crystallization was carried out at 120° C. for 8 h. The solid product was separated, second dried at 80° C. for 3 h, and calcined at 400° C. for 10 h to obtain a LTA structure hollow aluminum phosphate molecular sieve.

[0043] Example 3

[0044] 1) 4.09 g of aluminum isopropoxide, 0.046 g of phosphoric acid aqueous solution (85 wt %) and 0.004 g of hydrofluoric acid aqueous solution (40 wt %) were sequentially added to 7.2 g of deionized water, and the mixture was stirred at 150 r / min for 15 min in an ice bath at 0° C. to obtain a premixed solution; 2.32 g of propylene oxide (PO) was added dropwise at 30 drops / min to the premixed solution, and the mixture was stirred at 200 r / min for 5 min at 25° C., and then 5 g of tetramethylammonium hydroxide (TMAOH) and 10 g of 1-butyl-3-methylimidazole hydroxide ([Bmim]OH) were sequentially impregnated, and the mixture was covered with a PE film to produce a sealing condition, and the mixture was stirred at 300 r / min for 30 min at 35° C. to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel is 1:0.02:0.002:1:10 (the molar amounts of the aluminum source and the phosphorus source are calculated in the form of their oxides).

[0045] 2) The hydrogel was placed in a mold with a diameter of 9 cm and dried at 120° C. for 2 h to obtain aluminum phosphate dry gel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the aluminum phosphate dry gel was 1:0.02:0.002:1:5 (the molar amounts of the aluminum source and the phosphorus source were calculated according to their oxide forms).

[0046] 3) 0.50 g of aluminum phosphate dry gel was placed in a 30 mL polytetrafluoroethylene liner, first crystallized at 240° C. for 4 h, and dried at 90° C. for 2.5 h to finally obtain nano aluminum phosphate molecular sieve powder.

[0047] 4) 0.30 g of nano aluminum phosphate molecular sieve powder was placed in 5.0 g of tetrapropylammonium hydroxide (TPAOH) aqueous solution (the concentration of the template agent tetrapropylammonium hydroxide was 0.05 mol / L), and the second crystallization was carried out at 240° C. for 4 h. The solid product was separated, second dried at 120° C. for 1 h, and calcined at 600° C. for 2 h to obtain a LTA structure hollow aluminum phosphate molecular sieve.

[0048] Example 4

[0049] 1) 4.09 g of aluminum isopropoxide, 4.61 g of phosphoric acid aqueous solution (85 wt %) and 0.40 g of hydrofluoric acid aqueous solution (40 wt %) were sequentially added to 14.4 g of deionized water, and the mixture was stirred at 60 r / min for 5 min in an ice bath at 0° C. to obtain a premixed solution; 11.6 g of propylene oxide (PO) was added dropwise to the premixed solution at 60 drops / min, and the mixture was stirred at 60 r / min for 10 min at 15° C., and then 5.0 g of tetrapropylammonium hydroxide (TPAOH) and 7.0 g of 1-ethyl-3-methylimidazole hydroxide ([Emim]OH) were sequentially impregnated, and the mixture was covered with a PE film to produce a sealing condition, and the mixture was stirred at 60 r / min for 20 min at 50° C. to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel is 1:2:0.2:5:20 (the molar amounts of the aluminum source and the phosphorus source are calculated in the form of their oxides).

[0050] 2) The hydrogel was placed in a mold with a diameter of 9 cm and dried at 80° C. for 10 h to obtain aluminum phosphate dry gel. The molar ratio of Al2O3:P2O5:HF:H2O in the aluminum phosphate dry gel was 1:2:0.2:5:10 (the molar amounts of the aluminum source and the phosphorus source were calculated according to their oxide forms).

[0051] 3) 0.50 g of aluminum phosphate dry gel was placed in a 30 mL polytetrafluoroethylene liner, first crystallized at 110° C. for 36 h, and dried at 90° C. for 12 h to finally obtain nano aluminum phosphate molecular sieve powder.

[0052] 4) 0.30 g of nano aluminum phosphate molecular sieve powder was placed in 6.0 g of di-n-butylamine (the concentration of the template agent di-n-butylamine was 0.50 mol / L), and the second crystallization was carried out at 110° C. for 24 h. The solid product was separated, second dried at 90° C. for 12 h, and calcined at 450° C. for 10 h to obtain a LTA structure hollow aluminum phosphate molecular sieve.

[0053] Example 5

[0054] 1) 0.66 g of pseudo-boehmite, 4.60 g of phosphoric acid aqueous solution (85 wt%) and 0.50 g of hydrofluoric acid aqueous solution (40 wt%) were added to 7.2 g of deionized water in sequence, and the mixture was stirred at 120 r / min for 6 min in an ice bath at 5°C to obtain a premixed solution; 11.62 g of propylene oxide (PO) was added dropwise at 80 drops / min to the premixed solution, and the mixture was stirred at 240 r / min for 12 min at 30°C, and then tetraethylammonium hydroxide (TEAOH) and 1-butyl-3-methylimidazole hydroxide ([Bmim]OH) were impregnated in sequence, and the mixture was covered with a PE film to produce a sealing condition, and the mixture was stirred at 240 r / min for 30 min at 45°C to obtain a hydrogel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel is 1:4:0.5:10:20 (the molar amounts of the aluminum source and the phosphorus source are calculated in terms of their oxide forms).

[0055] 2) The hydrogel was placed in a mold with a diameter of 9 cm and dried for 6 h at 110° C. to obtain aluminum phosphate dry gel. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the aluminum phosphate dry gel was 1:4:0.5:10:10 (the molar amounts of the aluminum source and the phosphorus source were calculated according to their oxide forms).

[0056] 3) 0.50 g of aluminum phosphate dry gel was placed in a 50 mL polytetrafluoroethylene liner, first crystallized at 220° C. for 12 h, and dried at 110° C. for 1.5 h to finally obtain nano aluminum phosphate molecular sieve powder.

[0057] 4) 0.30 g of nano aluminum phosphate molecular sieve powder was placed in 5.0 g of 1-butyl-3-methylimidazole hydroxide ([Bmim]OH) aqueous solution (the concentration of the template agent 1-butyl-3-methylimidazole hydroxide ([Bmim]OH) was 0.20 mol / L), and the second crystallization was carried out at 90° C. for 36 h. The solid product was separated, second dried at 100° C. for 6 h, and calcined at 500° C. for 6 h to obtain a LTA structure hollow aluminum phosphate molecular sieve.

[0058] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a LTA structure hollow aluminum phosphate molecular sieve, characterized in that: The following steps are involved: (1) deionized water, an aluminum source, an aqueous phosphoric acid solution and an aqueous hydrofluoric acid solution are mixed, and stirred for the first time under ice bath conditions to obtain a premixed solution; propylene oxide is added dropwise to the premixed solution, and stirred for the second time, and then dual template agents are sequentially impregnated, and stirred for the third time under sealed conditions to obtain a hydrogel; (2) The hydrogel in step (1) is first dried to obtain aluminum phosphate xerogel; (3) The aluminum phosphate dry gel in step (2) is first crystallized and dried to obtain nano aluminum phosphate molecular sieve powder; (4) placing the nano aluminum phosphate molecular sieve powder described in step (3) in a template aqueous solution, performing a second crystallization, separating the solid product, performing a second drying, and then calcining to obtain a LTA structure hollow aluminum phosphate molecular sieve; The molar ratio of Al2O3:P2O5:HF:PO:H2O in the hydrogel described in step (1) is 1:0.02~50.0:0.002~5.0:0.2~100.0:0.5~1000.0; the dual template agent described in step (1) is two of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, 1-ethyl-3-methylimidazole hydroxide, 1-butyl-3-methylimidazole hydroxide, 1-propyl-3-methylimidazole hydroxide or 1-pentyl-3-methylimidazole hydroxide, which are respectively immersed in the two dual template agents in turn; The concentration of the template in the template aqueous solution in step (4) is 0.001-100.0 mol / L, and the template is one of tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, di-n-butylamine, 1-ethyl-3-methylimidazole hydroxide, 1-butyl-3-methylimidazole hydroxide, 1-propyl-3-methylimidazole hydroxide or 1-pentyl-3-methylimidazole hydroxide.

2. The preparation method according to claim 1, characterized in that: The aluminum source in step (1) is one of crystalline aluminum chloride, pseudo-boehmite or aluminum isopropoxide.

3. The preparation method according to claim 1, characterized in that: The concentration of the phosphoric acid aqueous solution in step (1) is 70-99 wt %, and the concentration of the hydrofluoric acid aqueous solution in step (1) is 30-70 wt %.

4. The preparation method according to claim 1, characterized in that: In step (1), the speed of the first stirring is 5-1000 r / min, the temperature of the first stirring is -5-15°C, and the time of the first stirring is 1-360 min; the speed of the dropping in step (1) is 2-270 drops / min; the temperature of the second stirring in step (1) is 6-80°C, the speed of the second stirring is 5-1000 r / min, and the time of the second stirring is 1-360 min; the temperature of the third stirring in step (1) is 8-85°C, the speed of the third stirring is 3-1000 r / min, and the time of the third stirring is 1-600 min.

5. The preparation method according to claim 1, characterized in that: The temperature of the first drying in step (2) is 50-150° C., and the time of the first drying is 0.5-24 h. The molar ratio of Al2O3:P2O5:HF:PO:H2O in the aluminum phosphate dry gel in step (2) is 1:0.02-50.0:0.002-5.0:0.2-100.0:0.1-50.

0.

6. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the first crystallization is 90-300° C., and the time of the first crystallization is 1-240 h. In step (3), the temperature of the drying is 25-200° C., and the time of the drying is 0.5-36 h.

7. The preparation method according to claim 1, characterized in that: The temperature of the second crystallization in step (4) is 25-300°C, and the time of the second crystallization is 0.5-240 hours; the temperature of the second drying in step (4) is 25-200°C, and the time of the second drying is 0.5-36 hours; the calcination in step (4) is carried out in air, the temperature of the calcination is 400-600°C, and the time of the calcination is 2-10 hours.

8. The LTA structure hollow aluminum phosphate molecular sieve prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the LTA structure hollow aluminum phosphate molecular sieve as claimed in claim 8 or the LTA structure hollow aluminum phosphate molecular sieve prepared by the preparation method according to any one of claims 1 to 7 in heterogeneous catalysis.

Citation Information

Patent Citations

  • Multi-level structure mesoporous zeolite material and preparation method thereof

    CN102050461A

  • Preparation of LTA structure aluminophosphate molecular sieve membrane supported by porous alumina carrier

    CN103318916A